Investigation On Lecturer Acceptance And Use Of E-portfolio In Tabuk University In Saudi Arabia - B, Alshammri Bander Mousa (2023)
In recent decades, the E-portfolio system has gotten much attention. An Eportfolio is a helpful tool for teaching, learning, and growth that involves lecturers and students and is backed up by feedback from the faculty. The study’s primary goal is to look at the factors affecting lecturers' accepting and using of E-portfolios at the University of Tabuk in Saudi Arabia. In order to provide a new, extended version of the unified theory of acceptance and use of technology, this study integrates the already-existing variables of performance expectation, effort expectancy, social influence, and enabling factors (UTAUT). Three new variables were introduced to the new expanded model: perceived triability from the Defining Issue Test (DIT) theory, computer self-efficacy from Systematic Concept Teaching (SCT) theory, and selfmanagement. This study used a quantitative approach, and the 292 respondents were lecturers from the University of Tabuk. The data collection, the researcher, constructed an online survey in Google Drive. The quantitative approach employed in this study comprises the examination of a particular subject for statistical data generation. The analysis was performed using Smart Partial Least Squire (Smart-PLS). The results show that behavioural intention is positively correlated with performance expectation, effort expectation, and self-management, but social influence, perceived triability, and computer self-efficacy are not. Furthermore, the utilisation of an E-portfolio is favourably associated with behavioural intention and enabling conditions. The fast transformation of the future, it may be argued, creates a problem for instructional planners and strategists.